EXPLORING THE SOCIO-ECONOMIC DETERMINANTS OF CHILD LABOR EXPLOITATION, GONDAR, NORTH WEST ETHIOPIA - Gebeyehu, Kelemu Fenta; Liyew, Alemayehu Mulat; Admas, Bewket Dereje; Bitew, Mastewal Abwa (Innovare Journal of Social Sciences, 2016)
Introduction: The issue of child labor abuse and exploitation becomes a serious problem at local, national and international level and in our context children are engaged in laborious and seriously exploitative working condition due to various socio- economic challenges. Objective: Hence, the main objective of this study was conducted to explore the major socio-economic determinants of child labor exploitation in Gondar town in the case of Arada Area. Methods: in doing this, we have employed mixed research method of survey for quantitative and key informant interview for qualitative research methods. The data was collected from 25 respondents (20 children, 2 residents and 3 non-governmental organizations) which were taken from purposively selected area. Results: The data collected revealed that parental and communal positive attitude towards child labor, low educational status of their family, poverty, early marriage, divorce, lack of community awareness towards child rights and illegitimacy of child labor, death of parents, migration and the presence of abusive working condition at home are the major socio- economic determinants of child labor exploitation in the study area.Â  Conclusion: Child labor exploitation is the result of various socioeconomic situations of children themselves, their families and the surrounding community. Key Words; Child labor Exploitation, Socio-economic determinants and child Â 